Potential biomarkers of atopic dermatitis - Yu, Ling; Li, Linfeng (Frontiers in Medicine, 2022)
Atopic dermatitis (AD) is a chronic, recurrent inflammatory skin disease with a wide range of heterogeneity. Accurate biomarkers or predictors will be the key to instructing personalized tailored precise treatment. The development of technology such as transcriptomics, genomics, and proteomics provides novel insights into the possibility to find potential biomarkers. Meanwhile, the emerging minimally invasive methods such as tape stripping were used to reveal different profiles of patients’ skin without biopsy. Several potential biomarkers or predictors have been found. In this review, we summarized the current development of potential biomarkers of atopic dermatitis. NOS2/iNOS, hBD-2, and MMP8/9 may be the candidate biomarkers for AD diagnosis. FLG gene mutation increased the occurrence risk of AD. FABP5 may serve as an effective biomarker for atopic march. SCCA2, TARC, CTACK, EDN, MDC, LDH, and IL-18 can be the candidate biomarkers for disease severity monitoring. IL-17, IL-23, IL-33, and IDO1 can be used as predictive biomarkers for AD comorbidities. LDH, TARC, PARC, periostin, IL-22, eotaxin-1/3, and IL-8 may be the candidate biomarkers for monitoring treatment effects. There are still unmet needs and a long way to go for more convenient, non-invasive and effective predictors and biomarkers to better guide personalized precise treatment.